(3cfR GdYQaGf aj abI GdbQBfs - (3CHi efUhQ GdMSf Hf jhSa jhSa Hf Ydj GHf GdeWgQ GdMdis
(3ChdgG (B:s
(3GdMeO ddg GdPi GfRd Ydi YHOg GdcJGH dcd TF HjJkG s
(3BNQgG (B:s
(3HGdQSe GdMSf ZjQ eMJGL Edi JUQjM HGdGSe hGdfSH LYd Gddg XdGdg eeOhOI s
(3GdfSNI HgG MhGTs
(3JcQQ CjVkG JMJ Qbe (B203 (3JaSjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1517s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs